Structural and Mechanical Properties of AZOY Thin Films Deposited on Flexible Substrates - Oliveira, C. (2008)
Transparent conducting Al doped ZnO films have been deposited by do magnetron sputtering, on class and polymer substrates at room temperature. Depositions have been carried out front an AZOY (contains a small amount of Y2O3 in addition to Al2O3 and ZnO) target under different conditions such as working pressure, substrate bias voltage and oxygen flow rate. The crystallinity of the Al doped ZnO films has been improved by using low-energty-ion bombardment. Likewise. the use of either the rotation or the static mode of the substrate during deposition influences the crystallinity and therefore the optical parameters and the electrical resistance of the films. Increasing. the thickness of the films reduces the threshold strain at which the films can be deformed without provoking significant changes on their electrical properties.